Agree to Disagree: Understanding the Failure of Mediation Facilitated by Paralegals - Yuli Prasetyo Adhi; Triyono Triyono; Dewi Sulistianingsih; Rahmawati Mohd Yusoff (Journal of Law and Legal Reform, 2026)
Mediation is widely recognized as an alternative dispute resolution mechanism that emphasizes consensus and mutually beneficial outcomes. However, mediation does not always result in a settlement agreement. This article examines the factors contributing to mediation failure, particularly in cases facilitated by paralegals. Using socio-legal research combined with qualitative analysis of mediation practices at the International Mediation and Arbitration Center (IMAC), the Indonesian National Arbitration Institute (BANI), the Gunungkidul Regency Government in Yogyakarta, and National Legal Reform Agency (BPHN), this study analyzes the role of paralegals, the dynamics of the disputing parties, and the procedural challenges that lead to deadlock during mediation. The research findings indicate that several factors, including a lack of good faith on the part of the parties, unrealistic expectations, communication barriers, power imbalances, and limited mediator competence, influence mediation failure. This study argues that mediation should not be considered a failure when no agreement is reached, as the process can still provide clarity for the parties and guide them towards alternative legal pathways. This research contributes to the dispute resolution discourse by highlighting the practical challenges faced by paralegals in the mediation process.